The Influence Of Performance Blocking Behavior And Economic Conditions On Auditor Employees' Career Development Interest at PT Telkom - Nur Khofifah Rauf; Masdar Mas’ud; Aryati Arfah (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Blocking Behavior refers to actions that obstruct or hinder an individual's performance in achieving specific goals. This can include actions or attitudes that directly or indirectly prevent individuals or groups from reaching desired outcomes, such as withholding information, delaying decisions, or creating obstacles in the work process. This study aims to examine the influence of Performance Blocking Behavior and Economic Conditions on the Career Development Interest of Auditor Employees at PT. TELKOM. The data in this study were obtained from Auditors working at PT. TELKOM who were willing to participate as respondents. The data collection method used in this research was primary data sources. The data collection technique employed was a questionnaire. The analysis requirements were tested through normality tests, multicollinearity tests, and heteroscedasticity tests. The data analysis technique used in this research was the two-predictor regression analysis or multiple regression analysis. The results of the study indicate that Performance Blocking Behavior and Economic Conditions have a positive and significant influence on the Career Development Interest of Auditor Employees both partially and simultaneously.